THE EFFECT OF TASK-BASED LANGUAGE TEACHING (TBLT) STRATEGY ON STUDENTS’ SPEAKING ABILITY IN DEMONSTRATIVE SPEECH - Aziz, Abdul (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2018)
The aim of conducting this research was to find out whether or not TBLT strategy has the effect of students’ speaking ability. The population was all of the eleventh grades students of MAN 2 Kota Bengkulu in academic year 2017/2018 that consist of 281 students. The sample of the research of this research was taken from class XI IPS 3 which consisted of 35 students and class XI IPS 4 which consisted of 35 students. The students were divided into two class, the experiment class and the control class. The experiment was given treatment by using TBLT strategy in teaching speaking about demonstrative speech, while the control class was given by using conventional technique. The pretest was given to the two groups before giving the treatment. The mean score of experimental group was 57.786 and the mean score of control class was 58.057. The result showed that sig.(2-tailed) 0.927 was higher than α-value (0.05). It means that the ability of both classes are not significant effect. After given the treatment for ten meeting in experimental class, the mean score of experimental class was 68.92 and the mean score of control class was 63.54. The result showed that sig.(2tailed) 0.02 was less than (0.05). It means that the alternative hypothesis accepted and null hypothesis is rejected. So the researcher concluded the TBLT strategy gave positive effect towards students’ speaking ability in demonstrative speech of MAN 2 Kota Bengkulu. Moreover, the problem of this research formulated in the question: Is there any significant effect on students’ speaking ability in demonstrative speech between the students who are taught using TBLT strategy and those of that who are not? The hypothesis of this research is there is significant effect on students’ speaking ability in demonstrative speech between the students who are taught using TBLT strategy and those of that who are not.